MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAM ACHIEVEMENT DIVISION) DALAM MENGUPAYAKAN TANGGUNG JAWAB SISWA [STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) COOPERATIVE LEARNING MODEL FOR STUDENT RESPONSIBILITY] - Sherly Yunia Taloen; Asih Enggar Susanti (Polyglot, 2023)
AbstractThe learning process that takes place in the classroom demands the responsibility of each student for learning to be active not passive so that the learning objectives can be achieved. However, students often lack this responsibility when they are learning in the classroom. This can be seen when some students focus on their activities and not all students contribute to discussions. One of the things that is done to strive for student responsibility is to apply a cooperative learning model of the Student Team Achievement Division (STAD) type. The present study aims to explain the steps of the STAD (Student Teams Achievement Division) cooperative learning model to seek student responsibility in the classroom. The research method used is descriptive qualitative. The conclusion of this research is that the STAD (Student Teams Achievement Division) type cooperative learning model is carried out with the following steps, explaining the material and learning objectives, dividing and directing students to work together in groups, and finally providing evaluation and appreciation of student work. Thus, the Student Teams Achievement Division type of cooperative learning model can strive for student responsibility.Bahasa Indonesia AbstrakProses pembelajaran yang berlangsung di dalam kelas, menuntut  tanggung jawab setiap siswa agar pembelajaran tidak pasif melainkan aktif sehingga dapat mencapai tujuan pembelajaran. Fakta yang ditemukan adalah kurangnya tanggung jawab siswa saat melakukan pembelajaran di dalam kelas. Hal ini terlihat dari sebagian siswa yang masih sibuk dengan kegiatan mereka masing-masing dan tidak semua anak berkontribusi untuk melakukan diskusi. Salah satu hal yang dilakukan untuk mengupayakan tanggung jawab siswa adalah menerapkan model pembelajaran kooperatif tipe student team achievement division. Penelitian ini bertujuan untuk menjelaskan langkah-langkah model pembelajaran kooperatif tipe STAD (Student Teams Achievement Division) untuk mengupayakan tanggung jawab siswa di kelas. Metode penelitian yang digunakan adalah kualitatif deskriptif. Kesimpulan dari penulisan penelitian ini adalah model pembelajaran kooperatif tipe STAD (Student Teams Achievement Division) dilakukan dengan langkah-langkah sebagai berikut, menjelaskan materi dan tujuan pembelajaran, membagi dan mengarahkan siswa untuk bekerja sama dalam kelompok, dan yang terakhir memberikan evaluasi serta penghargaan terhadap hasil kerja siswa. Sehingga, model pembelajaran kooperatif tipe Student Teams Achievement Division dapat mengupayakan tanggung jawab siswa.